Pengaruh Kemajuan Teknologi Terhadap Perilaku Sosial - MIFTAH KUSUMA DEWI (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2024)
Abstract Technology develops very quickly so that it has a significant impact on society. In the process of its development, technology has positive and negative impacts on society. Technological developments also affect patterns of human behavior. Technology is a tool that can facilitate solving problems in everyday human life. Human life can be helped by technology that is used wisely, but it will cause humans to experience various problems if it is not used according to its function. Technology facilitates human activities by meeting the needs they need for their survival. Technological developments can change social interaction to be more open. Moral degradation can occur due to technological developments that are not filtered and make the morale of the nation's next generation worse off. Various efforts can be made to address the impacts that occur due to technology that continues to develop. The use of technology in a positive direction is one of the efforts that can be made in reducing the negative impact of technology. Keywords: Impact, Technological Development, Social Behavior